Accidents by poisonous animals in the north of the province of La Pampa, Argentina. Epidemiological study (Veterinary Science, 2018)
They are of compulsory report in our country, because they produce serious consequences in Public Health. This project aims to epidemiologically describe accidents caused by poisonous animals in the north of La Pampa, identify the areas of highest risk and relate them to the distribution antivenoms centers and health institutions with intensive care. A retrospective descriptive epidemiological study was carried out to collect information about accidents with poisonous in the north of La Pampa province during the period 2005-2017. Primary and secondary data sources were used. A review of C2 reports of poisonous accidents from National Health Surveillance System (NHSS) and from records of the Dangerous Species for human and animal health Identification Services from FCV-UNLPam was carried out. Twentyeight interviews to community references and 10 health teams were done. According to the NHSS data, 6 cases of alacrism, 21 of arachnoidism and 3 of ophidism were recorded in the study period. According to the interviews, cases of poisonous animal accidents were described in different locations. The distribution centers of antivenoms, are according to the areas where the accidents were recorded. From the analysis of the data in the study period, we can conclude there are more underreporting than cases reported to the NHSS. In situations where data on accidents by venomous species are deficient, it is difficult to accurately determine the antidotes. This leads national health authorities to underestimate these needs, thereby reducing the distribution of anti-venoms. For this reason, it is important to strengthen the notification, systematization and dissemination of information to contribute to the monitoring and implementation of prevention measures and the treatment of accidents.
Keywords: poisonous accidents; report; epidemiology; prevention; antivenoms